The "Femme Fatale": A Literary and Cultural Version of Femicide - Segal, Naomi (Qualitative Sociology Review, 2017)
The figure of the femme fatale is understood as inviting her own murder. Supposedly, the cause of the violence done by a man in thrall to her, she is in fact the primary victim of this violence. In the French confessional narrative, the woman is always somehow at fault for the protagonist’s failure, whether by loving him too little or too much; she dies and he lives to tell the tale, recounting it to another man who listens and absolves. Thus, the heroine both dies again and is revived, to be contained — in both senses — in the text. Fictions from three centuries — Prévost’s Manon Lescaut (1753), Mérimée’s Carmen (1845), and Gide’s L’Immoraliste (1902) — will be compared for their representation of literary femicide. Almost a century later, the changed ending of Fatal Attraction (directed by Lyne in 1987) demonstrates the public’s clamor for the killing of a supposedly dangerous woman. A final section compares the significance of Princess Diana with these fictional instances of femicide: How did our love for her bring on her violent death?